2021
DOI: 10.1038/s41591-021-01564-7
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognitive and hypokinetic movement disorder with features of parkinsonism after BCMA-targeting CAR-T cell therapy

Abstract: Brief CommuniCation Nature MediciNeExtended Data Fig. 10 | immunohistochemistry showing BCMA protein expression in brain tissue of the patient and in a control brain. (a) BCMA immunohistochemistry of the caudate nucleus subependymal region (10x magnification, left, scale bar 200 µm). Inset (40x magnification, right, scale bar 50 µm) shows high magnification image of astrocytes (top) and a neuron (bottom) that stained positive for BCMA, whereas surrounding cells were negative. Images shown are representative sl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
75
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 138 publications
(89 citation statements)
references
References 28 publications
0
75
1
Order By: Relevance
“…However, that article did not present details on the development of their assay, such as staining results from orthogonally qualified BCMA-positive and BCMA-negative control samples, which would be needed to rule out nonspecific immunoreactivity. 24 As the mechanism underlying neurological symptoms remains undefined, evaluation of a large number of brain samples from myeloma patients with neurological symptoms is needed; however, the absence of BCMA protein detection in the present data suggests a low risk of direct on-target/ off-tumor cytotoxicity in the brain.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…However, that article did not present details on the development of their assay, such as staining results from orthogonally qualified BCMA-positive and BCMA-negative control samples, which would be needed to rule out nonspecific immunoreactivity. 24 As the mechanism underlying neurological symptoms remains undefined, evaluation of a large number of brain samples from myeloma patients with neurological symptoms is needed; however, the absence of BCMA protein detection in the present data suggests a low risk of direct on-target/ off-tumor cytotoxicity in the brain.…”
Section: Discussionmentioning
confidence: 60%
“…A recent case report described a patient who was treated with an anti-BCMA CAR-T therapy (ciltacabtagene autoleucel) and had neurological adverse events, including a movement disorder consistent with parkinsonism. 24 The authors examined this patient and one healthy subject and reported BCMA expression in neurons and astrocytes in the caudate nucleus, using a rabbit polyclonal antibody (US Biological B0807-50). However, that article did not present details on the development of their assay, such as staining results from orthogonally qualified BCMA-positive and BCMA-negative control samples, which would be needed to rule out nonspecific immunoreactivity.…”
Section: Discussionmentioning
confidence: 99%
“…Acute cerebral edema is probably the most serious and potentially life-threatening complication which was described after treatment with CAR T-cells against CD-19 [64]. Very delayed symptoms, such as progressive movement disorder with features of Parkinsonism approximately 3 months after infusion of CAR-T, were described also [65].…”
Section: Safety Of Car-t Cells In MM Therapymentioning
confidence: 99%
“…This other neurotoxicity occurred later with a median onset of 27 days with variable associate symptoms including a cluster of movement and neurocognitive treatment-emergent events. Further exploration to understand and minimize the frequency to this other neurotoxicity is ongoing and a recent description of BCMA expression on neurons and astrocytes in the basal ganglia may represent a possible mechanistic explanation (116). Most cases of ICANS can be managed successfully with a short course of corticosteroids.…”
Section: Toxicities Of T Cell Directed Therapymentioning
confidence: 99%